2008
DOI: 10.1002/joc.1590
|View full text |Cite
|
Sign up to set email alerts
|

The global footprint of persistent extra‐tropical drought in the instrumental era

Abstract: The major North American droughts as per instrumental records are shown to be part of a larger, global pattern of low‐frequency drought variability. Drought in western North America during the 1850s–1860s, 1870s, 1890s, 1930s and 1950s, is shown to coincide with the occurrence of prolonged dry spells in parts of Europe, southern South America and western Australia. Tropical land regions are mostly wet during these periods, with the exception of central east Africa, southern India and Sri Lanka, which are dry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…For example, due to the NAO Results of this study, which evidenced different trends between continental Europe and the Mediterranean basin, confirm past studies. Indeed, while in continental Europe dry periods have been identified in the 20th century [63][64][65], the 2000s have been characterized by an increase in drought frequency and severity in Southern Europe and the Mediterranean area [66,67], but also in some areas of Russia. In particular, Northern and Eastern Europe showed the highest drought frequency and severity from the early 1950s to the mid-1970s while Southern and Western Europe showed the highest drought frequency and severity from the early 1990s onwards [68,69].…”
Section: Resultsmentioning
confidence: 99%
“…For example, due to the NAO Results of this study, which evidenced different trends between continental Europe and the Mediterranean basin, confirm past studies. Indeed, while in continental Europe dry periods have been identified in the 20th century [63][64][65], the 2000s have been characterized by an increase in drought frequency and severity in Southern Europe and the Mediterranean area [66,67], but also in some areas of Russia. In particular, Northern and Eastern Europe showed the highest drought frequency and severity from the early 1950s to the mid-1970s while Southern and Western Europe showed the highest drought frequency and severity from the early 1990s onwards [68,69].…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies which attempt to cover more than one region (e.g. Calow et al, 2010;Herweijer and Seager, 2008;Rojas et al, 2011;Naumann et al, 2012;Tadesse et al, 2008;Verschuren, 2004). These and many other studies are comprehensively reviewed and discussed in the following sections.…”
Section: Masih Et Al: a Review Of Droughts On The African Continementioning
confidence: 99%
“…Nicholson, 2000). Many studies attempted to investigate the natural causes that could be associated with droughts in Africa (Caminade and Terray, 2010;Dai, 2011Dai, , 2013Giannini et al, 2008Hastenrath et al, 2007;Herweijer and Seager, 2008;Jury et al, 1996;Kerr, 1985;Lebel et al, 2009;Manatsa et al, 2008;Nicholson, 2000;Richard et al, 2001;Shanahan et al, 2009;Tierney et al, 2013;VicenteSerrano, 2012;Zeng, 2003). Some of them also focus on anthropogenic factors, such as climate change, aerosol emissions, land use practices and resulting land-atmosphere interactions, contributing to drought inducing mechanisms (e.g.…”
Section: Causes Of Droughtsmentioning
confidence: 99%
“…Recent research has shown that multi-year La Niña events are associated with persistent drought in the western USA (Cole et al 2002) as well as in southern Europe, southern South America, and western Australia (Herweijer & Seager 2008). A single-year La Niña is generally associated with a 15 to 30% decrease in winter precipitation, but it has a negligible effect on the summer monsoon.…”
Section: Comparison Of Causal Mechanismsmentioning
confidence: 99%